Brief Report: Number of Circulating Follicular Helper 2 T Cells Correlates With IgG4 and Interleukin‐4 Levels and Plasmablast Numbers in IgG4‐Related Disease. Issue 9 (September 2015) - Akiyama, Mitsuhiro; Suzuki, Katsuya; Yamaoka, Kunihiro; Yasuoka, Hidekata; Takeshita, Masaru; Kaneko, Yuko; Kondo, Harumi; Kassai, Yoshiaki; Miyazaki, Takahiro; Morita, Rimpei; Yoshimura, Akihiko; Takeuchi, Tsutomu
<x xml:space="preserve">Abstract</x> Objective To elucidate the pathologic role of follicular helper T (Tfh) cells and their subsets in active, untreated IgG4‐related disease. Methods Fifteen patients with active, untreated, biopsy‐proven IgG4‐related disease, 24 patients with primary Sjögren's syndrome (SS), 12 patients with allergic rhinitis, and 23 healthy controls were evaluated. Tfh cells were defined as CD3+CD4+CXCR5+CD45RA– cells. Circulating Tfh cell subsets among CXCR5+CD45RA–CD4+ T cells were defined as Tfh17 cells (CXCR3–CCR6+), Tfh1 cells (CXCR3+CCR6–), or Tfh2 cells (CXCR3–CCR6–). CD19+CD20–CD27+CD38+ cells were defined as plasmablasts. Serum cytokine levels (interleukin‐4 [IL‐4], IL‐10, IL‐21, and IL‐33) were measured by cytometric bead array or enzyme‐linked immunosorbent assay. Results Patients with IgG4‐related disease had significantly increased levels of Tfh2 cells compared to healthy controls or patients with primary SS or allergic rhinitis. Increased Tfh2 levels were strongly associated with increased serum IgG4 levels and the IgG4:IgG ratio in IgG4‐related disease. A positive correlation was observed between Tfh2 counts, plasmablast counts, and serum IL‐4 levels. Interestingly, levels of plasmablasts and serum IL‐4 and IgG4 decreased after treatment with glucocorticoids, whereas no obvious change was observed in Tfh2 cell counts. Conclusion The Tfh2 cell count was specifically increased in IgG4‐related disease and was correlated with elevated serum levels of IgG4 and IL‐4 and plasmablast counts. Tfh2 cells were the only component that was not affected by glucocorticoid treatment, suggesting that Tfh2 cells are the cell type implicated in IgG4‐related disease.